2001
DOI: 10.5014/ajot.55.5.531
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Adaptation Model Versus Biomechanical–Rehabilitation Model in the Treatment of Patients With Hip Fractures

Abstract: Both groups benefited from occupational therapy intervention. Occupational Adaptation was associated with a more efficient outcome and greater patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…[78][79][80]91,148,180,191 Twenty studies compared intensive physical exercise with less intensive physical activity or an inactive control. 69,78,80,83,[91][92][93]104,[107][108][109][110]113,114,117,118,122,126,130,169 Twenty-four studies compared supervised programmes with conventional programmes that either did not include supervision as part of the programme or included only minimal supervision to ensure patient safety. 69,80,83,87,[91][92][93]104,[107][108][109][110][112][113][114]126,131,136,151,153,180,186,191,199 Nine studies compared specifically tailored programmes with generic rehabilitation programmes.…”
Section: Physical Activity Components Of the Rehabilitation Programmesmentioning
confidence: 99%
See 4 more Smart Citations
“…[78][79][80]91,148,180,191 Twenty studies compared intensive physical exercise with less intensive physical activity or an inactive control. 69,78,80,83,[91][92][93]104,[107][108][109][110]113,114,117,118,122,126,130,169 Twenty-four studies compared supervised programmes with conventional programmes that either did not include supervision as part of the programme or included only minimal supervision to ensure patient safety. 69,80,83,87,[91][92][93]104,[107][108][109][110][112][113][114]126,131,136,151,153,180,186,191,199 Nine studies compared specifically tailored programmes with generic rehabilitation programmes.…”
Section: Physical Activity Components Of the Rehabilitation Programmesmentioning
confidence: 99%
“…69,78,80,83,[91][92][93]104,[107][108][109][110]113,114,117,118,122,126,130,169 Twenty-four studies compared supervised programmes with conventional programmes that either did not include supervision as part of the programme or included only minimal supervision to ensure patient safety. 69,80,83,87,[91][92][93]104,[107][108][109][110][112][113][114]126,131,136,151,153,180,186,191,199 Nine studies compared specifically tailored programmes with generic rehabilitation programmes. 69,79,80,83,99,109,[113][114][115] Psychological components of the rehabilitation programmes Fourteen studies reported using a psychological intervention in isolation …”
Section: Physical Activity Components Of the Rehabilitation Programmesmentioning
confidence: 99%
See 3 more Smart Citations